OTORITAS HADIS AHAD DAN KRITERIA KESHAHIHANNYA PERSPEKTIF MUHAMMAD AL-GHAZALI DALAM KITAB AL-SUNNAH Al-AL-NABAWIYYAH BAIN AHL AL-FIQH WA AHL AL-ḤADĪṠ - Rustina N. Rustina N. (Jurnal Studi Islam, 2021)
This study aims to describe and analyze Muhammad al-Ghazali's thoughts on the authority of the hadith ahad and the criteria for authenticity of the hadith formulated in the book al-Sunnah al-Nabawiyah Baina ahl al-Fiqh wa Ahl al-Ḥadīṡ The main issues raised are 1) how Muhammad's thoughts al-Ghazali about the authority of the hadith ahad and the criteria for its authenticity, 2) how is the method of criticism of Muhammad al-Ghazali in relation to the understanding of the Prophet's Hadith. This type of research is library research, which uses literature in the form of books and articles as primary data sources and secondary data sources, data collection techniques are direct and indirect citations. The data analysis technique used is content analysis, which is an effort to describe and analyze in depth the content of written or printed information objectively and systematically. The results of this study are 1) Al-Ghazali set five criteria as requirements in the hadith to be accepted properly; three criteria related to sanad and two criteria related to matan (hadith material). The three criteria related to the sanad are; a. dhabit narrator, b. Fair narrator, c. Points one and two must be owned by all narrators in the sanad. He did not include the continuity of the chain as a criterion for the validity of the hadith, because according to him this element had actually entered into the criteria for point two. Criteria related to matan, are: a) Matter of hadith is not syā (one or more of the narrators contradict their narration with a narrator who is more accurate and more reliable), b) Matan hadith does not contain illat qadhihah, i.e. deficiencies that are known by hadith experts so they reject the history of a narrator. 2) Al-Ghazali's method in critiquing the hadiths goes through four steps, namely testing with the Qur'an, testing with Hadith, testing with historical facts, and testing with scientific truth.